Acute Postoperative Seizures and Engel Class Outcome at 1 Year Postselective Laser Amygdalohippocampal Ablation for Mesial Temporal Lobe Epilepsy. Issue 2 (6th August 2022) - Barkley, Ariana S.; Sullivan, Liam T.; Gibson, Alec W.; Zalewski, Kody; Mac Donald, Christine L.; Barber, Jason K.; Hakimian, Shahin; Ko, Andrew L.; Ojemann, Jeffrey G.; Hauptman, Jason S.
Abstract : BACKGROUND: MRI-guided laser interstitial thermal therapy (MRgLITT) for mesial temporal lobe epilepsy is a safe, minimally invasive alternative to traditional surgical approaches. Prognostic factors associated with efficacy are debated; preoperative epilepsy duration and semiology seem to be important variables. OBJECTIVE: To determine whether acute postoperative seizure (APOS) after MRgLITT for mesial temporal lobe epilepsy is associated with seizure freedom/Engel class outcome at 1 year. METHODS: A single-institution retrospective study including adults undergoing first time MRgLITT for mesial temporal lobe epilepsy (2010-2019) with ≥1-year follow-up. Preoperative data included sex, epilepsy duration, number of antiepileptics attempted, weekly seizure frequency, seizure semiology, and radiographically verified anatomic lesion at seizure focus. Postoperative data included clinical detection of APOS within 7 days postoperatively, and immediate amygdala, hippocampal, entorhinal, and parahippocampal residual volumes determined using quantitative imaging postprocessing. Primary outcome was seizure freedom/Engel classification 1 year postoperatively. RESULTS: Of 116 patients, 53% (n = 61) were female, with an average epilepsy duration of 21 (±14) years, average 6 failed antiepileptics (±3), and weekly seizure frequency of 5. APOS was associated with worse Engel class ( P = .010), conferring 6.3 times greater odds of having no improvement vs achieving seizure freedom at 1 year. Residual amygdala, hippocampal, entorhinal, and parahippocampal volumes were not statistically significant prognostic factors. CONCLUSION: APOS was associated with a lower chance of seizure freedom at 1 year post-MRgLITT for mesial temporal lobe epilepsy. Amygdala, hippocampal, entorhinal, and parahippocampal residual volumes after ablation were not significant prognostic factors. Abstract :